A small-molecule approach towards the Fountain of Youth: chemically induced pluripotent stem cells. Issue 11 (27th August 2022) - Luo, Tuoping
Abstract: Generation and regeneration as an answer to disease treatment has been around for some time. Yet never have we come so close to reaching such 'life-altering' capabilities. Today, the field of regenerative medicine research focuses on replacing non-functional or dead cells with healthy ones, in order to repair or regenerate tissues and organs to restore normal functions. Pluripotent stem cells have the ability of long-term self-renewal and possess the potential to differentiate to all kinds of functional cells in humans. Therefore, how to directly obtain a large number of pluripotent stem cells from patients in vitro, to be grown into differentiated specific tissues and organs, has become one of the most important topics. Six decades ago, Gurdon's group discovered that cell differentiation is a reversible process [1 ], laying down the foundation for cell reprogramming research. Commonly there are biological and chemical methods for the acquisition of pluripotent stem cells in vitro, which also aim to produce further differentiated specific tissues and organs. Fifteen years ago, Yamanaka's group first reported the acquisition of induced pluripotent stem cells (iPSCs) via overexpression of four transcription factors OSKM to the somatic cells [2 ]. Chemical reprogramming—using cell permeable small molecules to manipulate the cell fates—has also progressed significantly. Hongkui Deng at Peking University and his co-workers reported that a combination of small molecule compounds could induce pluripotent stem cells from mouse somatic cells with an induction efficiency as high as 0.2% in 2013 [3 ]. After long-term persistence and unremitting efforts, Deng's group announced the acquisition of chemically induced pluripotent stem cells (CiPSCs) from human fibroblasts through a step-wised chemical reprogramming strategy in 2022. This technology for preparing human CiPSCs solves the underlying technical bottleneck for the development of stem cells and regenerative medicine, and advances the application of cell reprogramming towards a new stage [4 ]. As the progress in human cell reprogramming led to sufficient resources of CiPSCs, chemically induced cell fate trans differentiation research also brought us surprises. Deng and colleagues not only demonstrated that small molecules can reprogram astrocytes into neurons in the adult mouse brain, which provides a potential approach for developing neuronal replacement therapies [5 ], but also constructed a bio-artificial liver device through directed differentiation of human pluripotent stem cells to hepatic cells [6 ]. Recently, Deng and colleagues established an efficient method for producing islet cells from human CiPSCs and demonstrated that these cells were able to ameliorate diabetes in non-human primates [7 ]. CiPSCs might be considered to have potential in the fields of cell therapy, drug screening and disease modeling, and are the most critical 'seed cells' in the field of regenerative medicine. Emerging as important regulators of cell fate, natural product small molecules and their derivatives have played an important role in Deng's work. NSR spoke to Hongkui Deng about the highlights and possibilities of the field.